(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
The objectives of this work are to investigate the use of different eco-technologies as strategies for immobilization of redox enzymes on conductive carbon-based felts, to produce bio-functionalized textiles for a future use in sustainable applications while maintaining low environmental impact. Methods using cold remote plasma, electrically conductive biocompatible coating (PEDOT:PSS) and natural crosslinker for the enzyme (genipin) were tested and showed to be efficient in the intended applications. The enzymatic activity of the used glucose oxidase was maintained for multiple number of uses, and showed potential in sustainable wastewater treatment applications in bio-Fenton and bio-electro-Fenton setups.